2004
DOI: 10.1080/j003v18n01_11
|View full text |Cite
|
Sign up to set email alerts
|

Student Development in an Online Post-Professional Master's Program

Abstract: SUMMARY Students' perceptions of personal and professional development in an online post-professional Master's degree program in occupational therapy were investigated. In-class postings, reflection papers, and e-mail surveys completed by 14 occupational therapists throughout the course of an online Master's program were coded and analyzed. Three themes were identified: the developmental process of post-professional education, the value of the online learning community, and the influence of positive and negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In describing this phenomenon, participants’ language varied from “joining a guild” to “being cool.” We did not know that we needed digital music until others invented and Steve Jobs perfected it. Community is a key component of professional formation, and like Richardson,7 we demonstrated that it is attainable in a part-time program. The live-seminar components of this program reinforced connections made in an online environment and fostered future networking.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In describing this phenomenon, participants’ language varied from “joining a guild” to “being cool.” We did not know that we needed digital music until others invented and Steve Jobs perfected it. Community is a key component of professional formation, and like Richardson,7 we demonstrated that it is attainable in a part-time program. The live-seminar components of this program reinforced connections made in an online environment and fostered future networking.…”
Section: Discussionsupporting
confidence: 55%
“…Distance learning and asynchronous delivery were proposed as solutions if technical considerations could be addressed. Richardson presented a detailed account of occupational therapists who participated in a postprofessional master’s program 7. This was a distance-learning degree focused on clinical practice and investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies that have compared undergraduate and graduate students in traditional versus online courses, the outcomes are often measured by student and faculty selfreports, test grades, and final course grades (e.g., Allen et al, 2006;Clark, 2002;Farber, 2013;Fredda, 2000;Hong, 2002;Johnston, 2008;Means et al, 2009;Neuhauser, 2002;Phye, 1997;Richardson, 2004;Van Schaik, Barker, & Beckstrand, 2003;Weiss, Schreuer, Jermias-Cohen, & Josman, 2004). Collectively, these studies' findings revealed no significant difference in learning outcomes between students who were enrolled in traditional and online programs.…”
Section: Student Learning Outcomesmentioning
confidence: 99%
“…Graduatesacknowledgedthetransformationalnatureof theeducationalexperiencethatresultedinbothpersonaland professional growth (Richardson, 2004). They expressed feelingsofprofessionalrenewalandincreasedpride:"Igained anincreasedanddeeperunderstandingofourprofessionas wellasarenewedrespectforthepowerofoccupation";"The yearpriortoenteringtheprogram,Ifeltdisillusionedwith thefieldofoccupationaltherapy.IdidnotfeelIwaspracticingoccupationaltherapy.Whileattendingandsincegraduation,Inolongerhavethosefeelings";"Ilostmy'origins'or meaningofwhatbeinganoccupationaltherapistwas...I regainedthatknowledgeandpridewhileattendingthemaster'sprogram.…”
Section: Discussionmentioning
confidence: 99%
“…Theliteraturesuggeststhatpostprofessionaleducation produces both tangible and intangible benefits to participantsandthatgraduatesofpostprofessionalprogramsgoon toexpandtheirprofessionalengagementsandcontributions, therebybenefitingtheirprofession.Inaddition,literatureon onlineprogramssuggeststhattheycanbeeffectiveinprovidingappropriateeducationalchallengesandhigherlevellearningopportunitiesforadultlearners.Onlinepostprofessional master's-degreeprogramscanbeaviableeducationaloption for occupational therapists balancing work and family responsibilities. Apriorqualitativestudyofthefirstcohortofstudentsin ourpostprofessionalmaster's-degreeprogram (Richardson, 2004)documentedstudentperceptionsofthepersonaland professional transformations they experienced in the program.However,wehadnodataonwhethertheseperceptions translatedintoprofessionalengagementandcontributionsto thefield.Therefore,thepurposeofthisstudywastoevaluate theprofessionalactivitiesandperceptionsofprogrambenefits of occupational therapists who had obtained a masters of science(MS)degreeinourpostprofessionalonlineprogram. Inadditiontoin-classdiscussions,a"TownSquare"is accessibletoallstudentsandfacultyintheprogramwhere informationanddiscussionsofgeneralinterestareposted.…”
Section: Online Educationmentioning
confidence: 99%